Use of Native Yeast Strains for In-Bottle Fermentation to Face the Uniformity in Sparkling Wine Production - Vigentini, Ileana; Barrera Cardenas, Shirley; Valdetara, Federica; Faccincani, Monica; Panont, Carlo A.; Picozzi, Claudia; Foschino, Roberto (Frontiers in Microbiology, 2017)
The in-bottle fermentation of sparkling wines is currently triggered by few commercialized Saccharomyces cerevisiae strains. This lack of diversity in tirage yeast cultures leads to a prevalent uniformity in sensory profiles of the end products. The aim of this study has been to exploit the natural multiplicity of yeast populations in order to introduce variability in sparkling wines throughout the re-fermentation step. A collection of 133 S. cerevisiae strains were screened on the basis of technological criteria (fermenting power and vigour, SO2 tolerance, alcohol tolerance, flocculence) and qualitative features (acetic acid, glycerol and H2S productions). These activities allowed the selection of yeasts capable of dominating the in-bottle fermentation in real cellar conditions: in particular, the performances of FX and FY strains (isolated in Franciacorta area), and OX and OY strains (isolated in Oltrepò Pavese area), were compared to those of habitually used starter cultures (IOC18-2007, EC1118, Lalvin DV10), by involving nine wineries belonging to the two Consortia of Appellation of Origin. The microbiological analyses of samples have revealed that the indigenous strains showed an increased latency period and a higher cultivability along the aging time than the commercial starter cultures do. Results of chemical analyses and sensory evaluation of the samples after 18 months sur lies have shown that significant differences (P <0.05) were present among the strains for alcoholic strength, carbon dioxide overpressure and pleasantness, whereas they were not observed for residual sugars content, titratable acidity or volatile acidity. Indigenous S. cerevisiae exhibited comparable values respect to the commercial starter cultures. The ANOVA has also proven that the base wine formulation is a key factor, by significantly affecting (P <0.01) some oenological parameters of wine, like alcoholic strength, volatile acidity, carbon dioxide overpressure, titratable acidity and dry extract. The use of native yeast strains for the re-fermentation step can be considered a convenient way for introducing differentiation to the final product without modifying the traditional technology. In a perspective of “precision enology”, where the wine is designed on specific vine cultivars and microorganisms, this work underlines that exploring yeast biodiversity is a strategic activity to improve the production.